Organ-specific quantitative genetics and candidate genes of phenylpropanoid metabolism in Brassica oleracea - Marta eFrancisco; Mahmoud eAli; Mahmoud eAli; Federico eFerreres; Diego A. Moreno-Fernández; Pablo eVelasco; Pilar eSoengas (Frontiers in Plant Science, 2016)
Phenolic compounds are proving to be increasingly important for human health and in crop development, defense and adaptation. In spite of the economical importance of Brassica crops in agriculture, the mechanisms involved in the biosynthesis of phenolic compounds presents in these species remain unknown. The genetic and metabolic basis of phenolics accumulation was dissected through analysis of total phenolics concentration and its individual components in leaves, flower buds and seeds of a double haploid (DH) mapping population of Brassica oleracea. The quantitative trait loci (QTL) that had an effect on phenolics concentration in each organ were integrated, resulting in 33 consensus QTLs controlling phenolics traits. Most of the studied compounds had organ-specific genomic regulation. Moreover, this information allowed us to propose candidate genes and to predict the function of genes underlying the QTL. A number of previously unknown potential regulatory regions involved in phenylpropanoid metabolism were identified and this study illustrates how plant ontogeny can affect a biochemical pathway.